Evaluation of aqueous extract of syzygium polyanthum leaves as anti-hypertensive agent in spontaneous hypertensive rat (SHR) - Ramli, Nurul Syahida (2021)
Hypertension is associated with significant morbidity and mortality. The use of medicinal herbs as alternative medicines to manage hypertension is increasing exponentially. Syzygium polyanthum, has been claimed traditionally as an antihypertensive agent. This study aimed to determine the antihypertensive effects of the aqueous extract of S. polyanthum (AESP) leaves and its mechanisms using spontaneously hypertensive rats (SHR). The phytochemical profiling, antioxidant properties and antihypertensive activity were evaluated. Fifty male SHR were divided equally into 5 groups; untreated-SHR, Losartan-treated, 3 groups of AESP-treated with different dosages (1500 mg/kg, 1750 mg/kg and 2250 mg/kg), and 10 male WKY rats as control. All treatments were given orally for 12th weeks. Systolic blood pressure (SBP) was measured biweekly. Whereas, the biochemical analysis, oxidative stress markers and angiotensin-converting enzyme (ACE) level were evaluated at the end of the study. The histology of thoracic aorta and kidney were assessed using haematoxylin & eosin (H&E) staining, and scanning electron microscope (SEM). AESP contains flavonoids and phenols with gallic acid detected. AESP showed high in vitro antioxidant and ACE-inhibitory activities. In AESP-treated SHR; SBP reduced significantly, improved renal function and oxidative stress markers. However, only AESP (2250 mg/kg) significantly reduced ACE concentration. There was also histology improvement of the thoracic aorta and renal in AESP-treated SHR. Hence, the study suggests that antihypertensive properties of AESP are due to its antioxidant(mainly gallic acid) and ACE inhibitory activity. Thus, this study reveals the antihypertensive mechanism of AESP exerted inhibitory activity through suppression of the ACE action which might involved RAAS pathway.